Role of nanostructured networks as analytical tools for biological systems - Pandey P.C.; Chauhan D.S.; Singh V. (My University, 2025)
In recent years, nanostructured materials have emerged as potential candidates offering excellent prospects for interfacing the detection of biomolecules. Nanomaterials such as nanoparticles, nanostructured silicates, nano-sized metal oxides, nanostructured polymers, quantum dots, nanocomposites and sensing nanodevices are being utilized worldwide for fabrication of chemical sensors and sensor arrays with tailored characteristics and tuneable properties. Among above, the materials that create a matrix structure at the nanoscale level are particularly fascinating. The exceptional physical, chemical, mechanical and electrical properties of these matrices advocate their application in the electrode modification resulting in sensing devices and transducers with superior performance. Here we present an overview of different types of nanostructured networks that are applied in sensor development. The role of these materials in chemical sensors is described along with the techniques that are the backbone of the sensing process. Special attention has been given to some key sensors that are directly related to human physiology and have clinical significance.